Absolute Form: Modality, Individuality and the Principle of Philosophy in Kant and Hegel - Hoffmann, Thomas Sören, (Critical Studies in German Idealism ;, 2021)
"Knowing precisely what philosophy actually is, is itself a matter of philosophical science. It is knowledge of the idea of philosophy that is explicit to itself; knowledge's cognition of itself in the separation of its beginning and its end, from which difference its precise determination follows, is not itself a knowledge "about something""--